2050. Proportion of hospital-onset infections expressing antibiotic resistant (AR) phenotypes in US Hospitals, 2018 – 2020. (15th December 2022) - Olubajo, Babatunde; Wolford, Hannah; Rose, Ashley; Natalie, McCarthy; Reddy, Sujan; Jernigan, John A; Baggs, James
Abstract: Background: Reports suggest the COVID-19 pandemic in 2020 was associated with increases in hospital-onset AR infections, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus spp., carbapenem-resistant Enterobacterales ( E. coli, Klebsiella spp., and Enterobacter spp.) (CRE) and Acinetobacter spp. (CRAsp), extended-spectrum cephalosporin resistance suggestive of extended-spectrum β-lactamase producing Enterobacterales (ESBL-E), and multidrug-resistant Pseudomonas aeruginos a (MDR-PA). To evaluate whether trends were similar for susceptible and resistant strains, we estimated the proportions of these resistant phenotypes in U.S. hospitals. Figure 1. Proportion of hospital-onset pathogens expressing resistant phenotypes, 2018 – 2020 Methods: We analyzed 2018–2020 hospital microbiology data in the Premier Healthcare and BD Insights Research Databases. Hospital-onset (HO) infections were those with positive cultures collected after hospital day 3. We used a raking procedure to produce weights to match national hospital characteristics, specifically: U.S. census division, bed size, teaching status, age, gender and urban/rural designation. We used a weighted means survey procedure for annual national estimates and generated annual comparisons with multivariable logistic regression adjusted by hospital characteristics. Results: In 589 hospitals, the percentages of HO ESBL-E and CRAsp increased from 2019 to 2020 (Table). Among enterococci, the percentage with vancomycin resistance decreased. The percentages of MRSA, CRE, and MDR-PA did not change. Conclusion: Our findings suggest pandemic-related factors, such as changes in antibiotic use or infection control, may have differentially affected susceptible and resistant phenotypes of hospital pathogens. Increases in the percentages of HO CRAsp and ESBL-E suggest these resistant phenotypes may have had a selective advantage over susceptible strains during the pandemic. In contrast, no changes in the percentages of HO MRSA or MDR-PA were observed, suggesting that infection rates increased similarly for resistant and susceptible strains. These findings underscore the importance of strategies to prevent hospital-associated infections and AR that are resilient to pandemic-related stresses on the healthcare system. Disclosures: All Authors : No reported disclosures.